Manuel Fernández-Götz and Dirk Krausse (eds). Eurasia at the Dawn of History: Urbanisation and Social Change / Tamar Hodos (ed.). The Routledge Handbook of Archaeology and Globalization - Donnellan, Lieve (Journal of Greek Archaeology, 2018)
Connectivities are the focus of a lot of current Ancient World research. Either indirectly, as constituting one of many factors involving socio-cultural transformations with a heavy spatial impact, such as urbanisation processes, or directly, being at the very heart of transformative processes detectable in the archaeological record, such as globalisation, connectivity has become a new framework with which to approach the past. The advantage of connectivity as a concept is that it is broad, neutral and that it stimulates cross-cultural comparison.